Alive without a brain: Acrania/anencephaly, anhydraminios, abdominal-ascites, amelia and agenesis of the kidneys - M. Adam Afodun; J. Gashegu; K. Khadijah Quadri; A. Mustapha Masud; A. Imam; M. Fernendez Edgar; S. Odoma; S. Olatayo Okeniran (Rwanda Medical Journal, 2023)
A gravid middle-aged woman viewed on ultrasound demonstrated a viable anencephalic fetus at 25 weeks gestational age. The absence of the bilateral cerebral hemisphere, cranial vault, anhydramnios, abdominal ascites, and phaco-rhizomelia was discovered. We discuss evidencebased quadra –amelia in a non-consanguineous (negroid) couple of a 25-week prenatal scan. Apart from amelia on all four limbs, the fetus had abdominal ascites with other dysmorphic features. Tetramelia is known to be caused by mutation of the WNTB gene; in close relative intermarriages. A diagnosis of ascites, amelia, anencephaly/acrania, and anhydramnios was made, and the prognosis was documented in this report.